2010
DOI: 10.1093/nar/gkq236
|View full text |Cite
|
Sign up to set email alerts
|

Two novel families of plasmids from hyperthermophilic archaea encoding new families of replication proteins

Abstract: Thermococcales (phylum Euryarchaeota) are model organisms for physiological and molecular studies of hyperthermophiles. Here we describe three new plasmids from Thermococcales that could provide new tools and model systems for genetic and molecular studies in Archaea. The plasmids pTN2 from Thermococcus nautilus sp. 30-1 and pP12-1 from Pyrococcus sp. 12-1 belong to the same family. They have similar size (∼12 kb) and share six genes, including homologues of genes encoded by the virus PAV1 from Pyrococcus abys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
107
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 69 publications
7
107
0
Order By: Relevance
“…All integrase genes from known crenarchaeal viruses are of the SSV type. This type of gene is also found on some archaeal plasmids (21,34). The pNOB8-type integrase was found to be encoded on archaeal plasmids (6) and in putative proviruses of the Euryarchaeota (11).…”
mentioning
confidence: 84%
“…All integrase genes from known crenarchaeal viruses are of the SSV type. This type of gene is also found on some archaeal plasmids (21,34). The pNOB8-type integrase was found to be encoded on archaeal plasmids (6) and in putative proviruses of the Euryarchaeota (11).…”
mentioning
confidence: 84%
“…However, PAV1 shares several genes with plasmids from the Thermococcales (3 genes with Thermococcus nautilus plasmid pTN2 and an additional gene with Pyrococcus sp. strain JT1 plasmid pRT1) (254,284), suggesting a dynamic genetic interaction between these different types of mobile elements (253). Haloarchaeal virus His1 was first assigned to the family Fuselloviridae, which includes crenarchaeal viruses of similar morphology (16).…”
Section: Euryarchaeal Virusesmentioning
confidence: 99%
“…A number of Thermococcus and Pyrococcus strains have been isolated from hydrothermal vents in the Atlantic, Indian, and Pacific Oceans, and a systematic screening for extrachromosomal genetic elements revealed that a large proportion of archaeal isolates carry plasmids. Fifteen plasmids have been isolated and characterized so far, and they fall into six different groups based on their putative replication proteins (184,185).…”
Section: Genomic Featuresmentioning
confidence: 99%
“…The other replication protein is family specific. In the pTN2 family, a Prim/Pol enzyme, represented by PolpTN2, was characterized recently (165,184). The N-terminal domain of the protein showed both primase and DNA polymerase activities.…”
Section: Genomic Featuresmentioning
confidence: 99%
See 1 more Smart Citation